PROBLEMATIKA JURU SITA DALAM MELAKSANAKAN TUGAS DI PENGADILAN AGAMA NANGA PINOH: Perspektif Undang-Undang Nomor 50 Tahun 2009 Tentang Perubahan Kedua Atas Undang-Undang Nomor 7 Tahun 1989 Tentang Peradilan Agama - Sofian, Sofian; Marluwi, Marluwi; Ulya, Nanda Himmatul (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
The objectives of this study are: 1) To find out the problems of the bailiff at the Nanga Pinoh Religious Court in carrying out their duties. 2) To find out whether the bailiff at the Nanga Pinoh Religious Court has carried out his duties in accordance with Law Number 50 of 2009 concerning the second amendment to Law Number 7 of 1989 concerning Religious Courts. The results of the study can be concluded as follows: 1) The problems of the bailiff at the Nanga Pinoh Religious Court in carrying out their duties, namely the infrastructure that is less supportive, because there are villages that do not have road access for motorbikes to pass, during the rainy season natural disasters such as floods and landslides, the names of the parties are different between the nicknames and the names on the ID cards, making it difficult for the bailiff to find the litigants and in divorce cases the address of one of the parties is difficult to find. 2) The bailiff at the Nanga Pinoh Religious Court is only in charge of summoning the litigants. The bailiff at the Nanga Pinoh Religious Court has also carried out his duties in accordance with Law No. 50 of 2009 concerning the Second Amendment to Law No. 7 of 1989 concerning the Religious Courts, judging by the number of cases at the Nanga Pinoh Religious Court in 2021 which have completed 1 cases of polygamy permits, 39 cases of divorce divorce, 119 cases of litigation, 2 cases of joint property, 1 case of child control, 5 cases of guardianship, 18 cases of marriage legality, 87 cases of dispensation for marriage, 11 cases of guardian adhol and 2 cases of determining heirs. where the bailiff has a very important role in resolving the case.